2016
DOI: 10.1136/heartjnl-2016-310099
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic phenotype in osteogenesis imperfecta varies with disease severity

Abstract: Cardiovascular effects are identifiable in childhood even in mild forms of OI. Aortic dilation was the predominant finding, while valvular abnormalities were infrequent. Patients with more severe skeletal pathology (types 3/4) have more significant findings. Aortic and LV dilation in type 1 vs type 3/4 appears to differ based on the biochemical mechanism of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Few records of conditions unrelated to hearing loss were identified ( n = 2). Most records included adults [ 13 , 29 , 31 , 89 , 90 , 93 , 96 , 101 , 106 , 111 , 115 , 116 , 122 , 123 , 190 , 212 , 215 219 ] Cardiovascular 15 Records provided clinical heart measurements ( n = 11) and information on valvular disease ( n = 8), while heart failure ( n = 2), hypertension ( n = 3) and atrial fibrillation ( n = 1) were not well-described [ 13 , 29 , 139 , 142 , 151 , 170 , 175 , 182 184 , 220 – 224 ] Pulmonary 11 Four records described breathing problems and respiratory disease. Few data on wheezing ( n = 2) and respiratory arrest ( n = 1) were identified.…”
Section: Resultsmentioning
confidence: 99%
“…Few records of conditions unrelated to hearing loss were identified ( n = 2). Most records included adults [ 13 , 29 , 31 , 89 , 90 , 93 , 96 , 101 , 106 , 111 , 115 , 116 , 122 , 123 , 190 , 212 , 215 219 ] Cardiovascular 15 Records provided clinical heart measurements ( n = 11) and information on valvular disease ( n = 8), while heart failure ( n = 2), hypertension ( n = 3) and atrial fibrillation ( n = 1) were not well-described [ 13 , 29 , 139 , 142 , 151 , 170 , 175 , 182 184 , 220 – 224 ] Pulmonary 11 Four records described breathing problems and respiratory disease. Few data on wheezing ( n = 2) and respiratory arrest ( n = 1) were identified.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies of children with osteogenesis imperfecta have shown variable cardiac findings, including increased aortic diameter, diastolic dysfunction, and electrophysiological alterations. 4,8,15 Rush et al 7 conducted a cohort study with 100 children diagnosed with osteogenesis imperfecta that also paired 100 controls using body surface area. They reported larger aortic diameter, larger left ventricle internal diameter, and smaller left ventricle mass in children with osteogenesis imperfecta type 1 compared to their controls.…”
Section: Discussionmentioning
confidence: 99%
“…6 The aorta and most arteries are also rich in collagen types III and I, and many cardiac problems are associated with collagen matrix accumulation, depletion, or restructuring, such as those caused by type III and V collagen alterations, fibrillin I alterations, and those responsible for the aortic diseases associated with Marfan syndrome and Ehlers-Danlos syndrome. [6][7][8] Osteogenesis imperfecta has been described primarily as a bone disorder, but recent studies have suggested that its morbidity and mortality are often related to secondary cardiac and respiratory problems, although skeletal deformities are still the main problem. Myocardial dysfunction and valve disease have been described in many osteogenesis imperfecta cases, mainly in adults.…”
Section: Introductionmentioning
confidence: 99%
“…In a small sample study, OI children were found to have greater dimensions of the main aorta and LVEDd than control group, but without significant change in heart function ( 31 ). Compare with control group, OI children exhibited larger LV internal dimensions and dilated main pulmonary arteries ( 32 , 33 ). Our study confirmed the alterations of heart and aorta in OI children, including larger internal diameters of MPA and left heart chambers, with lower LVEF than BSA-matched healthy children.…”
Section: Discussionmentioning
confidence: 85%
“…In a small sample study, OI children were found to have greater dimensions of the main aorta and LVEDd than control group, but without significant change in heart function (31). Compare with control group, OI children exhibited larger LV internal dimensions and dilated main pulmonary arteries (32,33).…”
Section: Other Genes Mutationsmentioning
confidence: 81%